Fundamentals of selling : customers for life - Futrell, Charles (Boston : Irwin/McGraw-Hill, 2002)
In this text the author draws on his own experience as a sales professional rather than from a theoretical perspective. He continues to develop contemporary themes such as relationship selling and technology around his classic approach.
Includes indexes.
Keywords: Selling